Hubungan Gaya Belajar Mahasiswa Dengan Prestasi Belajar Mahasiswa Pada Kampus V UNM PGSD Parepare Pada Mata Kuliah Bahasa Inggris - Abdul Halik; Sayidiman Sayidiman; Muhammad Asrul Sultan (Publikasi Pendidikan, 2017)
Each Students has different learning styles, learning styles as a way of learning habits of students in a lesson, which greatly affect the learning outcomes of students. The purpose of this research was to determine the relationship of auditory learning styles of students with the achievement of students at UNM Campus V PGSD Pare Pare on the subject of English. This type of research used in this study is a correlation study. This research is located in the Campus V UNM Faculty of Education UPP PGSD Parepare and the population in this study is the UPP students PGSD Parepare force in 2015, amounting to 63 people consisting of three classes and 33 used as a sample in this study. Techniques used data collection using observation technique, documentation, questionnaire and value students' achievement in the subject of English. The technique of analyzing data using descriptive statistic data analysis and correlation analysis. Conclusions about the relationship auditory learning styles of students and academic achievement in English language learning students UPP PGSD Pare Pare, shows that there is a correlation between auditory learning styles of students and academic achievement in English language learning students UPP PGSD Pare Pare.Keywords: Correlation study, auditory learning style